2006
DOI: 10.1074/jbc.m512723200
|View full text |Cite
|
Sign up to set email alerts
|

A Metabotropic Glutamate Receptor Family Gene in Dictyostelium discoideum

Abstract: Metabotropic glutamate receptors (mGluRs) are a class of G-protein-coupled receptors that possess a seven transmembrane region involved in the modulation of excitatory synaptic transmission in the nervous system. mGluR orthologs have been identified in Drosophila, Caenorhabditis elegans, and higher organisms. Drosophila possesses two mGluR genes, DmGluRA and DmXR. We screened the Dictyostelium genome data base using the ligand binding domain of rat mGluR1 as bait, and identified a new receptor, DdmGluPR, belon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 17 publications
2
30
0
Order By: Relevance
“…2A), with the same results acquired when cells were developed on buffer-saturated filters (data not shown). This is consistent with a previous study which reported that the presence of 1 mM GABA or glutamate had no effect on the cAMP chemotactic response (20). We also tested the ability of cells to migrate directionally toward a wide range of GABA gradients (1 nM to 10 mM) using a micropipette assay.…”
Section: A Gaba B Receptor-like Protein Grlb Is Involved In Earlysupporting
confidence: 74%
See 4 more Smart Citations
“…2A), with the same results acquired when cells were developed on buffer-saturated filters (data not shown). This is consistent with a previous study which reported that the presence of 1 mM GABA or glutamate had no effect on the cAMP chemotactic response (20). We also tested the ability of cells to migrate directionally toward a wide range of GABA gradients (1 nM to 10 mM) using a micropipette assay.…”
Section: A Gaba B Receptor-like Protein Grlb Is Involved In Earlysupporting
confidence: 74%
“…Briefly, vegetative cells were washed three times with 10 ml MES buffer (20 7 vegetative cells were washed twice with cold MES buffer and suspended in 1 ml of cold MES buffer. The cells were lysed by passing through an Acrodisc 5 m pore size syringe filter (Pall).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations